(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
The article analyzes the findings of a cross-sectional study conducted at the Department of Dentistry of the Bukhara State Medical Institute. The study aimed to assess oral health and treatment needs among children with hearing and speech impairments. The sample included 124 students from specialized boarding schools in the Bukhara region, comprising 78 boys and 46 girls aged 6 to 18 years, with an average age of 12.95 years.. . A cross-sectional study was conducted to evaluate the oral health status and treatment needs of children with hearing and speech impairments at the Department of Dentistry, Bukhara State Medical Institute.